Fogo e queimadas: histórico, risco e calendário meteorológico na Amazônia Oriental. - SODRÉ, Giordani Rafael Conceição (Universidade Federal do Pará, 2020)
The use of fire as a way of cleaning the soil is widely inserted in the productive process of the Amazon, being one of the elements that drive the agricultural expansion in the region. This research aimed to analyze the general scenario of burning in the Amazon region in order to address the complexity that surrounds this theme, as it can be treated as a social problem, but with reflections on the climate issue. We analyzed the legal parameters of the use of fire in agricultural practices and a meteorological calendar was developed indicating when the environmental conditions are most favorable for the safer use of this practice. The results indicated that the current scenario of burning in the Amazon may be related to a combination of choices, how the issue of burning could have been addressed and how it actually was. Indicating that the main tools are aimed at combating the effects of burning and not its origin. He observed that tools such as the Fire Risk Index used by INPE have its reduced accuracy, because it considers only environmental variables, not including the action of man as a parameter, which limits the efficiency in anticipating the occurrence of a burn. Analysis of the latest research has pointed to the use of controlled fire as the most viable option for changing the current scenario, so the main approach of this research was to create a safe weather management calendar for field fire use. . The conclusion of this research shows that environmental education is the most effective way to combat the excessive use of burning, but this is an investment for the future. For the current scenario the creation of a burning calendar based on local monthly rainfall variability, allowing the burning to be performed at times more favorable to its unwanted propagation. Thus, the number of uncontrolled fires can be effectively reduced and biodiversity and economic losses can be reduced. This being the way to go while environmental education does not fulfill its role in changing this culture within the Amazon region.